Microstructure and enhanced seebeck coefficient of textured Sr3Ti2O7 ceramics prepared by RTGG method. Issue 12 (September 2016) - Qin, Mengjie; Gao, Feng; Wang, Min; Wang, Li; Dong, Gaogao; Huang, Xixi
Abstract: Textured Sr3 Ti2 O7 ceramics (abbreviated as S3T) with grain orientation degree higher than 0.7 were successfully prepared by reactive-templated grain growth (RTGG) technique combined with tape casting process, using plate-like Sr3 Ti2 O7 particles as templates. The phase transition, microstructure and thermoelectric properties were investigated. As the sintering temperature and soaking time increase, the density and texture fraction of ceramics increase. Textured Sr3 Ti2 O7 ceramics were sintered in air and annealed in argon + graphene carbon (Ar+C) atmosphere. The results showed that the resistivity of textured Sr3 Ti2 O7 ceramics annealed in Ar+C environment decreased significantly (seven orders of magnitude). After the annealing process, the texture fraction decreased, and Sr3 Ti2 O7 phase on the surface of textured ceramics decomposed to SrTiO3 . The Seebeck coefficient was negative, and the absolute value of S increased with increasing temperature. Textured Sr3 Ti2 O7 ceramics showed the maximum Seebeck coefficient (−399 μV/K) at 1073 K, which is higher than those of non-textured Sr3 Ti2 O7 -based materials.